Needs for family caregivers of Cerebrovascular Accident survivors - Jaine Kareny da Silva; Karla Ferraz Anjos; Jeorgia Pereira Alves; Darci de Oliveira Santa Rosa; Rita Narriman Silva de Oliveira Boery (Investigación y Educación en Enfermería, 2020)
Objective. To know the needs of family caregivers of Cerebrovascular Accident survivors.